Mobile Robotic-Arm Development for a Small-Scale Inter-Room Logistic Delivery using 2D LIDAR-guided Navigation - Hadha Afrisal; Ghanis Kauchya Nugraha; Aan Aria Nanda; Ahmad Didik Setiyadi; Olimjon Toirov; Rifky Ismail; Wahyul Amien Syafei; Munawar Agus Riyadi; Iwan Setiawan (TEKNIK, 2022)
This research aims to develop a low-cost mobile robotic arm for an indoor delivery system. Current pandemic and possible future threat of communicable disease become challenging scenarios in developing an unmanned logistic delivery system with a minimum human involvement, especially for inter-room items delivery inside a highly regulated building such as in hospital, clinic, pharmaceutical, foods and beverages industries. In this paper, a prototype of mobile robotic arm is designed to achieve an autonomous level of navigation utilizing a 2D LIDAR with a guided remote monitoring and control of object selections for loading/unloading process. The mobile robotic arm is an integrated robotics system of mobile robot with an attached robotic arm in its body. The base of the mobile robotic arm utilizes a differential-drive wheels configuration equipped with wheels odometry system. The robotic arm is configured of a 4-DoF SCARA-like structure. The 2-dimensional environment map is generated using LIDAR sensor utilizing Hector SLAM method prior to navigation. The autonomous navigation is performed using a 2D LIDAR-based technique by employing an A* algorithm for path planning and tracking mechanism. Experimental works were conducted in a small building environment consisting of some rooms and narrow corridors. The result of experiments show that the prototype of mobile robotic arm can safely and effectively navigate through the testing environment, subsequently to load and unload objects from one room to another room without colliding to objects and obstacles.